Moderating Role of Initiative on the Relationship Between Intrinsic Motivation, and Self-Efficacy on Entrepreneurial Intention - Ogba, Francisca N.; Ogba, Kalu T. U.; Ugwu, Lawrence E.; Emma-Echiegu, Nkechi; Eze, Adaobi; Agu, Solomon Amaechi; Aneke, Bernard Akonam (Frontiers in Psychology, 2022)
The growing population of new graduates and the increasing scarcity of employment opportunities have made entrepreneurship an unavoidable option for employment and self-sustenance. This study investigates the effect of the initiative in moderating the relationship between intrinsic motivation, self-efficacy, and entrepreneurship intention through the integrated framework of theory of planned behaviour, self-determination, and humanism. This study contributes insights to how these factors moderated by initiative influence entrepreneurial intention among graduating students of tertiary institutions in Nigeria. This study adopted a cross-sectional design to examine the moderating role of initiative on the relationship between intrinsic motivation, and self-efficacy on entrepreneurial intention among Nigerian graduates. A total number of 688 graduate students, including 266(38.6%) males and 422(61.4%) females with a mean age of 24.30 years (SD = 3.69), participated in the study. Participants responded to a self-report questionnaire containing Initiative, Intrinsic motivation, self-efficacy, and entrepreneurial intention scales. Results showed that all the variables correlated positively with entrepreneurial intention. Furthermore, initiative moderated the relationship between self-efficacy and entrepreneurial intention (value and start-ups/operations), such that high self-efficacy with high initiative showed higher entrepreneurial intention (value). While to those with low self-efficacy and low initiative, high self-efficacy with high initiative showed higher entrepreneurial intention (start-ups/operations) compared to low self-efficacy and low initiative. The study highlighted the role of initiative in transforming young graduates' entrepreneurial intention into full-fledged entrepreneurs.